A novel botryoidal aramid fiber reinforcement of a PMMA resin for a restorative biomaterial. (9th March 2017) - He, Xinye; Qu, Ying; Peng, Jinrong; Peng, Tao; Qian, Zhiyong
Abstract : A novel botryoidal PMMA microsphere-grafted aramid fiber system is developed to effectively strengthen PMMA restorative biomaterial. Abstract : Poly(methyl methacrylate) (PMMA) resin is widely used as a prosthetic and restorative biomaterial, such as in bone cement, denture base resin, etc . The flexural and compressive strength of a PMMA resin is of great concern and many approaches have been made to improve the flexural resistance and compressive strength of PMMA. To strengthen PMMA via high-performance (HP) fibers is a feasible way; however, the HP fibers are not very satisfactory in practice, with a complex handling process and esthetic concerns. The aim of this study is to investigate the preparation of a novel botryoidal PMMA microsphere-grafted aramid fiber system, which has never been reported before, and the flexural and compression behavior of the PMMA/aramid composite, and evaluate the cytotoxic effects of the PMMA/aramid composite. As a result, the addition of a microsphere-grafted aramid fiber to an acrylic resin, with the esthetic problem of the aramid fiber minimized, simultaneously improves the mechanical properties and the safety of the PMMA/aramid composite in vitro is proven acceptable, suggesting that the novel composite has great potential in the field of restorative materials in clinical applications where high mechanical properties are required such as hard tissue repairing.